Analisis Strategi Pengelolaan Organisasi Pada Lembaga Pendidikan di Jakarta - Ahmad Muksin; Nurhaliza Putri; Tasya Dwi Melani; Hamdun Hibatulloh; Fadhilah Nur Rohmah; Ditha Linggar Parawansa (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Organizational design and management strategies are key aspects in achieving the success of educational institutions. An effective organizational design must be able to support the vision, mission, and goals of the institution, while management strategies must be able to direct resources, time, and energy in the right direction to achieve these goals. To find answers to the problem formulations that have been determined in this study, the researchers decided to collect data using the library research method. The impact factor of the management strategy of educational institutions in Jakarta on the performance and effectiveness of the institution includes all forms, effects, influences, and consequences of the output of graduates of educational institutions on the social life of the community, culture, economy, local/national politics, security/peace of the community.